Perbandingan Biodiesel Hasil Transesterifikasi Minyak Biji Kepayang (Pangium Edule Reinw) Dengan Katalis NaOH Dan H-Zeolit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Biodiesel is a renewable alternative fuel produced from vegetable oils or animal through a transesterification reaction with the aid of a catalyst. One of the sources of vegetable oils that have the potential to be developed in Indonesia as biodiesel is oil seed kepayang, plant kepayang is a crop which is used as a cooking oil replacement for coconut oil and also as a raw material alternative biodiesel production, in which the seeds have an oil content enough high. Kepayang oil yield ranged from 46.43 to 51.81% w / w with the method of extraction solvent n-hexane (Ayu, 2008). This study aimed to compare the results of the transesterification reaction by using two different catalysts are NaOH (Homogeneous Catalysts) and H-zeolite (Heterogeneous Catalysts). And this study aims to create biodiesel from the seeds kepayang, studying the influence of the amount of catalyst NaOH and H-zeolite (1%, 2%, 3%) of the amount of biodiesel produced, studied the effect of mole ratio of methanol-oil (3: 1, 6: 1, 9: 1) to the amount of biodiesel produced and identify the characteristics of biodiesel from oil seeds kepayang. Maximum biodiesel yield is 31.0% obtained in the condition of the methanol-oil mole ratio 3: 1 with the use of 1% H-zeolite catalyst. Characteristics of biodiesel from the seeds drunk with H-zeolite catalyst has acid number of 0.67 mg-KOH / g, density of 879 kg / m3, viscosity of 5.87 mm2 / s and consists of 3.42% methyl palmitate, methyl linoleic 11.98 %, 16.90% methyl oleate and methyl steareat 2%. While the highest yield is 17.4% NaOH catalyst with methanol-oil mole ratio of 3: 1 and the catalyst 1%. With the characteristics of biodiesel have acid number of 0.50 mg-KOH / g, density of 860 kg / m3, viscosity of 3.42 mm2 / s and consists of methyl palmitate 3.72%, 12.49% methyl linoleic, oleic methyl 18.94% and steareat 1.94%.Keywords: biodiesel, kepayang seed oil, catalysts NaOH and H-Zeolite